أصول التفسير عند عبد هللا به عمر رضي هللا عنهما في تفسير القرآن - Andri Nirwana AN (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2014)
Basically, ushul at-tafsir is the science of Tafsir that describes the methods used  by the ancient interpreter in the digging secrets contained in the Qur'an in order to know  the laws of the Shari'ah, and bring benefit intended by Al Qur 'an. In this case, the science  of Tafsir is a collection of rules and foundations that help the interpreter to explore the  secrets of the Qur'an according to the human ability to uncover the lessons, as well as the  validity level, arguments from the Qur'an . In this case, the science of Ushul commentary  explains the meaning of understanding, experiences and secrets of the Qur'an and  determine methods to figure it out, and put the rules and principles that interpreter can  execute these methods in his interpretation.